2018
DOI: 10.3906/elk-1708-179
|View full text |Cite
|
Sign up to set email alerts
|

Wide bandwidth CMOS four-quadrant mixed mode analogue multiplier using a second generation current conveyor circuit

Abstract: The current mode responses show ± 150 µ A dynamic range with a maximum THD value about 0.083% and large bandwidth expanded from 2.67 GHz to 3.12 GHz.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…4 shows the results of the simulation test of thetransfer (DC) characteristics of the proposed multiplier circuit in the case whenthe input currents are continuously changed in the range from −100 up to +100 μA.Based on this, it can be concluded that the linearity in the transfer characteristicis provided in this range, while the maximum value of THD is about 0.1%. Theproposed multiplier provides a simpler configuration then the circuits described in[3, 19, 31–35], while the low power consumption (<1 mW) employs only asingle VDTA. For these reasons, the proposed multiplier configuration can be usedfor the realisation of variable gain amplifiers, adaptive filters, phase‐lockedloops, amplitude modulators, squarer and frequency doublers [31].…”
Section: Simulation and Experimental Resultsmentioning
confidence: 99%
“…4 shows the results of the simulation test of thetransfer (DC) characteristics of the proposed multiplier circuit in the case whenthe input currents are continuously changed in the range from −100 up to +100 μA.Based on this, it can be concluded that the linearity in the transfer characteristicis provided in this range, while the maximum value of THD is about 0.1%. Theproposed multiplier provides a simpler configuration then the circuits described in[3, 19, 31–35], while the low power consumption (<1 mW) employs only asingle VDTA. For these reasons, the proposed multiplier configuration can be usedfor the realisation of variable gain amplifiers, adaptive filters, phase‐lockedloops, amplitude modulators, squarer and frequency doublers [31].…”
Section: Simulation and Experimental Resultsmentioning
confidence: 99%
“…1b. By considering transistors M 1 and M 2 are identical, the relationship between the input and the output cur-rents is given in [15] as the following equations for the simple current mirror circuit for which the equivalent circuit given in Fig. 2a (…”
Section: Extended Bandwidth Symmetrical Otamentioning
confidence: 99%
“…The bandwidth of the circuit depends on the gate-source capacitance C gs and transconductance g m as given in Eq (2) [15].…”
Section: Extended Bandwidth Symmetrical Otamentioning
confidence: 99%
See 2 more Smart Citations